Adsorptive removal of sulfa antibiotics from water using spent mushroom substrate, an agricultural waste. Issue 1 (2nd January 2016) - Zhou, Aixia; Zhang, Yuling; Li, Rui; Su, Xiaosi; Zhang, Lanying
Abstract: The potential for spent mushroom substrates (SMS) to remove sulfa antibiotics (sulfas) from water was evaluated in a batch process. Experiments were carried out as a function of contact time, initial concentration (0.5–10 mgL −1 ), and pH (1–11). Adsorption isotherms were modeled using the Langmuir and Freundlich models. The data fit the Langmuir isotherm well. The maximum adsorption capacities were found to be 2.1072, 1.8103, 2.2991, and 2.2133 mg g −1 at 288 K for sulfamethyldiazine, sulfamethazine, sulfathiazole, and sulfamethoxazole, respectively. The kinetic data were analyzed using pseudo-first-order, pseudo-second-order, and intra-particle models. The results indicated that SMS could be an alternative to more costly adsorbents used for removal of trace sulfas.